Indo-European Time and the Perun-Veles Combat Indoevropski čas in boj med Perunom in Velesom - Lyle, Emily (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In Studia mythologica Slavica 11, I laid out some ideas about the Indo-European calendar and began to relate the gods of a suggested tenfold pantheon to my model of the year. In the present short note, I refer back to this earlier study with the aim of clarifying the calendar model and I add a tentative interpretation of the Perun-Veles combat as a version of the birth story of the young gods.